Does Oral Contraceptive Pill Influence Women's Mood and Stress Level? - Farideh Bastani; Ladan Mohammadi-Yeganeh (Iran University of Medical Sciences, 2009)
Background and Aim: Mood changes and high perceived stress, as the main controversial side effects of oral contraceptive pills (OCPs) may weaken women's desire for using these pills, thereby, increasing the occurrence of unwanted pregnancies which imposes financial and emotional costs to the families and society. The aim of this study was to investigate the effect of oral contraceptive pill on mood and perceived stress in women referred to family planning clinics.   Method and Material: This study with an experimental one group pretest-posttest design was conducted on forty six married women who were recruited with continuous sampling method. They were eligible candidates to use OCP with no previous experiences of hormonal contraceptive use for at least one year. Mood state and perceived stress were measured by the validated instruments of positive affect negative affect scale (PANAS) and perceived stress scale (PSS). The level of mood and perceived stress scores were compared before the intervention and within 3 month follow.   Results: There was no statistically significant differences between positive and negative mood and perceived stress pretest-posttest scores (P=0.133, P=0.756, P= 0.693).   Conclusion: The study findings suggest that consuming OCP(s) has no effects on the women's mood (with no previous positive history of psychological and mood disorder). In the case of sever mood changes in women using OCP regularly, providing educational and counseling programs regarding stress management as a healthy lifestyle could be beneficial. Furthermore, these strategies would be foundation in preventing unnecessary discontinuation of OCP and subsequent unwanted pregnancies as well as establishing stress management in women as the individuals with key roles in family and community.